2018
DOI: 10.1038/s41598-018-31122-0
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial DNA copy number is associated with psychosis severity and anti-psychotic treatment

Abstract: Mitochondrial pathology has been implicated in the pathogenesis of psychotic disorders. A few studies have proposed reduced leukocyte mitochondrial DNA (mtDNA) copy number in schizophrenia and bipolar disorder type I, compared to healthy controls. However, it is unknown if mtDNA copy number alteration is driven by psychosis, comorbidity or treatment. Whole blood mtDNA copy number was determined in 594 psychosis patients and corrected for platelet to leukocyte count ratio (mtDNAcnres). The dependence of mtDNAcn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 112 publications
2
18
0
Order By: Relevance
“…Yi et al reported that SOD activities were not altered after 6 weeks of lithium treatment ( 72 ), but Selek et al found opposite results in a similar study ( 34 ), suggesting that more research is needed in future. Similar inconsistent conclusions have also been reported in mtDNA copy number ( 70 , 73 ). A meta-analysis showed that there were small increases in peripheral BDNF levels after pharmacological treatment for manic episodes, and no significant changes before and after treatment for depressive episodes ( 8 ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Yi et al reported that SOD activities were not altered after 6 weeks of lithium treatment ( 72 ), but Selek et al found opposite results in a similar study ( 34 ), suggesting that more research is needed in future. Similar inconsistent conclusions have also been reported in mtDNA copy number ( 70 , 73 ). A meta-analysis showed that there were small increases in peripheral BDNF levels after pharmacological treatment for manic episodes, and no significant changes before and after treatment for depressive episodes ( 8 ).…”
Section: Discussionsupporting
confidence: 69%
“…Second, age is an important factor that may have an impact on these biological parameters. Oxidative stress, BDNF, and mtDNAcn were reported to be associated with age in patients with BD (68)(69)(70)(71). The biomarkers were only measured in young subjects with BD and healthy controls in this study, rather than comparisons in all age groups.…”
Section: Discussionmentioning
confidence: 91%
“…It included 41 studies, with 50 models to be applied either prenatally or at different times during NICU admission. After this publication, at least 8 new predictive models have been described [23][24][25][26][27][28][29][30] in a recent systematic review [31]. The most commonly used mortality predictive models today include CRIB I and II [4,32] (year 1993 / United Kingdom-first 12 hours of life; 2003 / United Kingdom-first hour of life), DRAPER [6] (2000 / United Kingdom-childbirth start and admission to NICU), SNAP II and SNAPPE II [7] (2001 / Canada-first 12 hours of life), NEOCOSUR [33] (2005 / South America-before admission to NICU), NICHD models [5,24] (2008 / USA-at the beginning of mechanical ventilation; 2012 / USA-sequential: at birth, 7th day of life, 28 days of life and 36 weeks postmenstrual), SAW [34] (2008 / Egypt-48 hours of life) and PREM Score [35] (2010 / United Kingdom-prenatal and birth).…”
Section: Discussionmentioning
confidence: 99%
“…We were also able to detect a cytotoxic activity when NSCs were exposed to ≥500 nM of clozapine. A cytotoxic activity for clozapine is well-established in the literature and has been observed in numerous in vitro [68,74,75] and in vivo studies [76]. Importantly, a study by Park et al [68], showed a neurotoxic activity when primary neurons were exposed to ≥10 μM of clozapine in vitro, the observed neurotoxic activity was also associated with increased apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 93%